EKSPLORASI WARNA ALAM KUNYIT UNTUK PRODUK MUKENA BATIK - Mursidah; Dheasari Rachdantia; Amin Sulistyowati (Canthing, 2022)
Natural dyes are non-toxic alternative dyes refurbished and environmentally friendly. Materials for natural dyes are selected based on its availability in nature and easy to obtain like turmeric (Curcuma domestica Val) which is a native spice and medicinal plant from Asian region. Turmeric is a plant that is commonly used as traditional medicine and herbal medicine. Apart from that, turmeric can also be used as a natural dye for batik cloth. This research aims to make turmeric an environmentally friendly natural dye for batik cloth, and produce a new product design with the idea of ​​providing additional use value to batik mukena products. The method used is qualitative research with a practice-based approach to the creative arts creation process (practice-led research). The results of this research are batik mukena products using the natural dye turmeric. Coloring using a dipping technique of 10 dips using natural turmeric dye with a fixation locking process using a tunjung. Keywords: Batik, Natural Turmeric Color, Mukena batik.